Concordance Between Life Satisfaction and Six Elements of Well-Being Among Respondents to a Health Assessment Survey, HealthPartners Employees, Minnesota, 2011 - Pronk, Nicolaas P. (Prev Chronic Dis, 2016)
INTRODUCTION: We assessed and tracked perceptions of well-being among employees of member companies of HealthPartners, a nonprofit health care provider and health insurance company in Bloomington, Minnesota. The objective of our study was to determine the concordance between self-reported life satisfaction and a construct of subjective well-being that comprised 6 elements of well-being: emotional and mental health, social and interpersonal status, financial status, career status, physical health, and community support. METHODS: We analyzed responses of 23,268 employees (of 37,982 invitees) from 6 HealthPartners companies who completed a health assessment in 2011. We compared respondents’ answers to the question, “How satisfied are you with your life?” with their indicators of well-being where “high life satisfaction” was defined as a rating of 9 or 10 on a scale of 0 (lowest) to 10 (highest) and “high level of well-being” was defined as a rating of 9 or 10 for 5 or 6 of the 6 indicators of well-being. RESULT: We found a correlation between self-reported life satisfaction and the number of well-being elements scored as high (9 or 10) (r = 0.62, P < .001); 73.6% of the respondents were concordant (high on both or high on neither). Although 82.9% of respondents with high overall well-being indicated high life satisfaction, only 34.7% of those indicating high life satisfaction reported high overall well-being. CONCLUSION: The correlation between self-reported life satisfaction and our well-being measure was strong, and members who met our criterion of high overall well-being were likely to report high life satisfaction. However, many respondents who reported high life satisfaction did not meet our criterion for high overall well-being, which suggests that either they adapted to negative life circumstances or that our well-being measure did not identify their sources of life satisfaction.